2023
DOI: 10.1097/icl.0000000000000989
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Benefits of Tear Exchangeable Limbal-Rigid Contact Lens Wear Therapy in Stevens–Johnson Syndrome Cases

Abstract: Objectives: To evaluate the long-term benefits of tear-exchangeable, limbal-rigid contact lens (CL) wear therapy in patients with Stevens-Johnson syndrome (SJS)-associated ocular sequelae. Methods: This retrospective study evaluated 50 eyes of 41 SJS patients (15 men and 26 women) who underwent limbal-rigid CL wear therapy for more than 2 years post fitting. Ocular sequelae (i.e., conjunctival hyperemia, corneal neovascularization, and upper tarsus scarring) before fitting and at 3 months, 6 months, 12 months,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…16 The long-term follow-up (mean follow-up period: 4.3±1.1 years) of limbal-rigid CL therapy for SJS showed VA improvement. 17 Moreover, the effectiveness of our new limbalrigid CL when used as a therapeutic modality post COMET for the treatment of severe OSDs was evaluated, and we found that the use of the lens reduced corneal irregularity and improved visual function. In addition, the limbal-rigid CL was found to have good wettability when worn, thus reducing eye pain related to severe dryness of the ocular surface and providing long-term stabilisation of the ocular surface.…”
Section: Clinical Sciencementioning
confidence: 98%
See 1 more Smart Citation
“…16 The long-term follow-up (mean follow-up period: 4.3±1.1 years) of limbal-rigid CL therapy for SJS showed VA improvement. 17 Moreover, the effectiveness of our new limbalrigid CL when used as a therapeutic modality post COMET for the treatment of severe OSDs was evaluated, and we found that the use of the lens reduced corneal irregularity and improved visual function. In addition, the limbal-rigid CL was found to have good wettability when worn, thus reducing eye pain related to severe dryness of the ocular surface and providing long-term stabilisation of the ocular surface.…”
Section: Clinical Sciencementioning
confidence: 98%
“…16 When a comparison was made between pre-CL fitting and 3 months after the initiation of the limbal-rigid CL-wear therapy, our findings revealed that conjunctival hyperaemia was decreased and that the reduction was maintained until the final follow-up examination performed at 5 years after the therapy was initiated. 17 Moreover, the design of the limbal-rigid CL in combination with proper and frequent use of artificial tears allowed each patient to wear the lens for more than 12 hours per day and avoid any pain associated with the extended usage. 6 21 Compared with at baseline, only a slight significant improvement in the condition of the OSGS corneal score was found at the final follow-up examination, and for unknown reasons, there was a slight reduction in corneal opacification.…”
Section: Clinical Sciencementioning
confidence: 99%